2015
DOI: 10.3171/2014.10.jns14343
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Metronomic Biofeedback Pump for leptomeningeal carcinomatosis: technical note

Abstract: Patients with leptomeningeal carcinomatosis face a particularly grim prognosis. Current treatment consists of intrathecal delivery of methotrexate (MTX) or cytosine arabinoside (Ara-C) via Ommaya reservoir or lumbar puncture. Yet despite these interventions, the median survival after diagnosis is only 4–7 months. To address inherent shortcomings of current treatments and provide a more effective therapeutic approach, the Pharmaco-Kinesis Corporation has developed a novel type of implantable pump capable of del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…16,17 Recently we have demonstrated that an implanted piezoelectric pump can be used in a leptomeningeal carcinomatosis model. 6 Thus, bypassing the BBB is critical and may be accomplished by several techniques.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Recently we have demonstrated that an implanted piezoelectric pump can be used in a leptomeningeal carcinomatosis model. 6 Thus, bypassing the BBB is critical and may be accomplished by several techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Wafer implants of the chemotherapeutic drug BCNU/carmustine, have been approved by the FDA and licensed for the treatment of malignant gliomas [36]. The Ommaya or Rickham reservoirs have been extensively used for intracavitary delivery [37,38] and new catheters and pump prototypes for CED have been recently developed [33,35,39].…”
Section: Discussionmentioning
confidence: 99%
“…Whether CED of bevacizumab can be used in long-term therapy may soon be addressed by the use of implantable programmable pumps currently in development. 5 Thus, the positive effects of bevacizumab on vessel reduction make CED of bevacizumab a more efficient and effective means of therapy.…”
Section: Discussionmentioning
confidence: 99%